Virtual water transfer patterns and water scarcity spillover risks of cities in the arid region of Northwest China - YANG Jingjing, MA Zhong, MA Weijing, JIAO Zhipeng, MAO Ting, WANG Ting (Ziyuan Kexue)
[Objective] This paper presents an analysis of the virtual water transfer patterns and water scarcity spillover risks of cities within the arid region of Northwest China. The aim is to inform the formulation of differentiated water resources management policies. [Methods] Based on the inter-city input-output tables of China for 2012 and 2017, this study employed a multi-regional input-output model, integrated with a water stress index, to systematically analyze the characteristics of virtual water flows, water dependency, and the spillover effects of water scarcity risks across 25 cities in the arid region of Northwest China. [Results] (1) Cities in the arid region of Northwest China were predominantly characterized by virtual water imports, particularly in the primary industry, a phenomenon closely linked to the region’s arid climate and economic structure. (2) Between 2012 and 2017, the total volume of virtual water imports increased significantly, while exports decreased, leading to a heightened dependency on water resources in net virtual water importing regions. (3) Cities facing higher water stress have transferred scarcity risks to other regions through virtual water trade to alleviate local pressures. By 2017, some cities’ water scarcity pressures and spillover risks showed signs of mitigation, due to policy adjustments, economic restructuring, and technological advancements. [Conclusion] The interregional transfer of virtual water resources has alleviated water stress in some cities, yet it has also triggered the regional spillover of water scarcity risks. Future research should incorporate multidimensional factors such as climate change, economic development, and policy shifts to further elucidate the interdependence and evolutionary patterns of water resources across regions. This will provide a theoretical foundation for the sustainable management of water resources in the arid region of Northwest China.